Post Operative Pain and Pain Management in Children After Dental Extractions Under General Anaesthesia - Chaudhari, Sudeep Madhusudan; Mishra, Anusuya; Mahajan, Ankit Santosh; Singh, Saurabh; Choudhary, Ruchika (Journal of Neonatal Surgery, 2025)
Background-The purpose of this research sought to ascertain the frequency, intensity, and length of postoperative discomfort among kids receiving general anaesthesia for dental procedures. Methodology-Thirty-three American Society of Anaesthesiology (ASA) Class I and II children aged four to six who needed several dental treatments, including at least one tooth extraction, pulpectomy, and/or pulpotomy of the primary dentition, were included in this prospective cross-sectional research investigation. Children with developmental delays, cognitive impairments, premature births, psychiatric drug usage, or documented starting pain or painkiller use were excluded. Results-According to the findings, 48.5% of patients experienced moderate-to-severe postoperative pain, which is characterised as FPS-R ≥ 6. Pain subsided over 3 days. Postoperative pain scores increased significantly from baseline (P < .001, Wilcoxon matched pairs signed rank test). Moderately good correlation between the 2 pain measures existed 2 and 12 hours from discharge (Spearman rhos correlation coefficients of 0.604 and 0.603, P < .005). Conclusion-Children do experience moderate-to-severe pain postoperatively. Although parents successfully used pain scales, they infrequently administered analgesics.